A study on the acceptance and use of Frog VLE among teachers in Malaysia / Fatin Adibah Ariffin - Ariffin, Fatin Adibah (Faculty of Business Management, 2017)
Malaysia is currently implementing the use of virtual learning environment in the education systems through the project of 1BestariNet. Under the project, the e-learning was integrated through a system called Frog VLE. This study was conducted to investigate the user acceptance in using the Frog VLE among teachers in Malaysia. To measure the user acceptance, the theory of unified theory of acceptance and use of technology (UTAUT) by Venkatesh was used as underpinning theory. From the theory, this study extracted four variables to measure the user acceptance which are performance expectancy, effort expectancy, facilitating conditions and social influence. Sampling technique used was convenience sampling and 285 valid questionnaires were collected. The findings were consolidated by five main analyses which were, reliability analysis, descriptive analysis, correlation analysis, regression analysis and cross-tabulation analysis. This study found that out of four independent variables, only performance expectancy that was not significant. All other variables have a significant relationship with each other. The study concludes that, level of acceptance towards Frog VLE are moderate. Hence, this paper proposed that Frog VLE should be improved based on the system’s highlighted weak points. Governments and related authorities also needs to maintain continuous monitoring and evaluation to ensure success of the implementation of Frog VLE in the future.